2007
DOI: 10.1002/ejlt.200600240
|View full text |Cite
|
Sign up to set email alerts
|

The source of dietary fatty acids alters the activity of secretory sphingomyelinase in the rat

Abstract: Secretory sphingomyelinase (sSMase) has been suggested to be involved in the development of cardiovascular diseases as well as other human pathologies. To deduce whether dietary fatty acid composition affects the circulating activity of this enzyme, we have compared its activity in serum from rats that had been given a diet containing either butter or a highly n‐6 polyunsaturated [grapeseed oil (GSO)] fat source for 14 wk. The results show that intake of GSO increases the activity of this ceramide‐producing en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…S-ASM activity is elevated in the plasma of APP/PS1 mice, while the concentrations of SM and ceramide are unchanged (Lee et al, 2014). Feeding rats grape seed oil vs. butter leads to increased S-ASM activity and, simultaneously, decreased ceramide concentrations (Drachmann et al, 2007). The induction of S-ASM activity by adeno-associated virus in ApoE -/-mice resulted in only minor changes in SM and ceramide: a small reduction of SM and ceramide in plasma at several time points after injection and a reduction of SM and unaltered ceramide concentrations in the liver (Leger et al, 2011).…”
Section: In Vivo Effects Of S-asm Activity On Sphingolipid Levelsmentioning
confidence: 99%
“…S-ASM activity is elevated in the plasma of APP/PS1 mice, while the concentrations of SM and ceramide are unchanged (Lee et al, 2014). Feeding rats grape seed oil vs. butter leads to increased S-ASM activity and, simultaneously, decreased ceramide concentrations (Drachmann et al, 2007). The induction of S-ASM activity by adeno-associated virus in ApoE -/-mice resulted in only minor changes in SM and ceramide: a small reduction of SM and ceramide in plasma at several time points after injection and a reduction of SM and unaltered ceramide concentrations in the liver (Leger et al, 2011).…”
Section: In Vivo Effects Of S-asm Activity On Sphingolipid Levelsmentioning
confidence: 99%
“…A few previous studies have found that LC-PUFA composition of breast-milk/formula, maternal RBC and umbilical cord blood was associated with the early QoM in term infants [18][19][20] as well as in preterm infants (born in gestational week [24][25][26][27][28][29][30][31][32][33][34][35][36] [17,35], but the investigated LC-PUFA indices and ratios vary and the results are not very consistent. None of these studies have tested the infants as shortly after delivery as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In brief: RBC were haemolysed in redistilled water, and the lipids were extracted by the Folch procedure [26]. Fatty acid methyl esters were produced from the extracted RBC lipids using a BF3-catalyzed method [27] and extracted with heptane and analysed by gas-liquid chromatography on an Agilent 6890 Series II chromatograph (Agilent Inc., Santa Clara, California, USA) equipped with a flame ionization detector and a SP2380 capillary column (length 60 m; internal diameter 0.25 mm and film thickness 0.2 µm from Supelco Inc, Pennsylvania, USA) [28]. Fatty acid peaks were identified using a standard mixture (Nu-Check Prep, Elysian, MN), and data are given as mass-% based on peak-area relative to the sum of all peak areas corrected for differences in detector-response.…”
Section: Blood Sampling and Fatty Acid Analysismentioning
confidence: 99%
“…DHA (C22:6, n-3) in plasma was analysed as described earlier [28]. Briefly, plasma lipids were extracted using a modification of the Folch-method, and fatty acid methyl esters (FAME) were produced using a BF 3 -catalyzed method, in which hydroquinone is added as antioxidant [29].…”
Section: Blood Analysismentioning
confidence: 99%
“…The method has been validated for DHA, and does not induce double-bond losses. The mass-percentage contribution of DHA to the total plasma FAME-pool was analysed using GC-FID, as described earlier [28].…”
Section: Blood Analysismentioning
confidence: 99%